Alaskan Berry Extracts Promote Dermal Wound Repair Through Modulation of Bioenergetics and Integrin Signaling - Esposito, Debora; Overall, John; Grace, Mary H.; Komarnytsky, Slavko; Lila, Mary Ann (Frontiers in Pharmacology, 2019)
Wild berry species which are endemic to Alaska and the circumpolar North exhibit unique medicinal properties that have long been appreciated by indigenous Arctic communities. Traditional use of Alaskan berry preparations in the treatment of skin wounds is recorded, but has not been scientifically evaluated. Alaskan wild berries contain diverse phytochemical compositions, featuring a variety of bioactive polyphenols which exhibit anti-inflammatory, antioxidant, and antimicrobial properties, making them ideal for wound healing interventions or natural anti-aging cosmeceutical formulations. Given increasing interest in identifying biologically active plant constituents for wound and skin care applications, the objective of this study was to screen crude, polyphenol-enriched, and fractionated extracts of several Alaskan wild berry species for skin wound healing properties: Empetrum nigrum (crowberry), Vaccinium uliginosum (bog blueberry), and Vaccinium vitis-idaea (low-bush cranberry or lingonberry). Cell migration assay with adult human dermal fibroblasts (HDFa), modeling skin wound closure, revealed that polyphenol-enriched bog blueberry extract most actively promoted migration, whereas divergent effects observed for other berry extracts corresponded with compositional disparities. LPS-stimulated inflammatory response assay in RAW 264.7 macrophages showed that reactive oxygen species (ROS) and nitric oxide (NO) production, as well as COX-2 and iNOS mRNA expression, were suppressed by most extracts, especially bog blueberry and proanthocyanidin (PAC) fractions. Wild berry germplasm contained abundant complex flavonoid structures such as PAC and anthocyanins (ANC), associated with improved repair and inflammatory resolution in these models. Next, underlying mechanisms by which PACs and bioactive metabolites (B2 dimer and epicatechin) could influence wound repair and aspects of skin regeneration were examined. PAC metabolites promoted scratch wound closure and appeared to exert highest impacts on early stages of wound healing through stimulating mitochondrial bioenergetics (basal respiration, ATP production, and maximum respiratory capacity) and upregulating expression of important ECM proteins (integrin-β1 and collagen type I α2 chain). Targeting cellular bioenergetics and integrin-mediated cell-ECM interactions with Alaskan wild berry compounds shows considerable therapeutic promise for chronic wounds or inflammatory skin disorders, as well as more generally to support regenerative healing responses and restore function in a variety of tissue and organ settings after injury or aging.